Overhaul dan Uji Performansi Generator Firman FPG1510 RV1-C - Hanni Maksum Ardi; Mokhamad Munir Fahmi; Nor Fajri; Yudistira Anugrahadi Wiraputra; Dibyo Setiawan; Toni Okviyanto (universitas teuku umar, 2026)
Electrical energy is one of the essential needs for garment entrepreneurs in Cileungsi, Bogor Regency, West Java, to support their production activities. However, frequent power outages in the region often disrupt the production process. The Firman FPG1510 RV1-C generator set (genset) can serve as a solution to overcome these outages, but the unit was found to be inoperable after initial evaluation. An overhaul maintenance was performed after component-level servicing failed to restore stable operation. The results of the overhaul process were evaluated through performance testing, which included fuel consumption testing under a 570Watt electrical load and exhaust emission measurements. The performance test results show that the highest fuel consumption rate (ṁbb) was 0.000089 kg/s at 3177 RPM. At the same speed, the highest brake specific fuel consumption (BSFC) was recorded at 0.21456 kg/kWh. The maximum electrical efficiency (ηt) was achieved at 3006 RPM with a value of 17.35%, while the highest brake thermal efficiency (BTE) was 43.45% at 2973 RPM. The emission test after overhaul produced CO levels of 0.92–2.72% and HC levels of 80–153 ppm, both of which comply with the Bandung City emission standards for gasoline engines (CO 4.5% and HC 1200 ppm). A comparison between the post-overhaul performance and the manufacturer’s specifications shows that the indicator shaft power after overhaul reached 1.42 kW at 3006 RPM, compared to 1.17 kW at 3000 RPM in the standard specification. This indicates a 21% increase in shaft power as a result of the overhaul maintenance.